2021
DOI: 10.1016/j.jbc.2021.100316
|View full text |Cite
|
Sign up to set email alerts
|

Conformational triggers associated with influenza matrix protein 1 polymerization

Abstract: A central role for the influenza matrix protein 1 (M1) is to form a polymeric coat on the inner leaflet of the host membrane that ultimately provides shape and stability to the virion. M1 polymerizes upon binding membranes, but triggers for conversion of M1 from a water-soluble component of the nucleus and cytosol into an oligomer at the membrane surface are unknown. While full-length M1 is required for virus viability, the N-terminal domain (M1NT) retains membrane binding and pH-dependent oligomerization. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Association of M1 with the plasma membrane triggers its oligomerization as a consequence of an increased affinity to other monomers, ultimately providing structural integrity and stability to the virion ( 43 45 ). The position of M1 T108 within the protein suggested a possible role in the regulation of M1-M1 interactions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of M1 with the plasma membrane triggers its oligomerization as a consequence of an increased affinity to other monomers, ultimately providing structural integrity and stability to the virion ( 43 45 ). The position of M1 T108 within the protein suggested a possible role in the regulation of M1-M1 interactions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed that the control of M1 multimerization involves phosphorylation at T108, probably by disturbing the interaction of T108 in monomer 0 with S157 contained in helix 8 of the interacting +1 monomer. M1 multimerization can also be restricted by known phosphorylation sites in the N-terminal region (S2/T5 and T9/Y10) ( 45 ), but experimental proof for their potential role in M1 multimerization has not yet been obtained. We propose that phosphorylation at T108 and also other residues allows for signal-guided, regulated, and reversible control of the M1 multimerization state.…”
Section: Discussionmentioning
confidence: 99%